A New Approach for Reliability Life Prediction of Rail Vehicle Axle by Considering Vibration Measurement - Bayraktar, Meral; Guclu, Rahmi; Tahrali, Necati (HINDAWI LTD, 2014)
The effect of vibration on the axle has been considered. Vibration measurements at different speeds have been performed on the axle of a running rail vehicle to figure out displacement, acceleration, time, and frequency response. Based on the experimental works, equivalent stress has been used to find out life of the axles for 90% and 10% reliability. Calculated life values of the rail vehicle axle have been compared with the real life data and it is found that the life of a vehicle axle taking into account the vibration effects is in good agreement with the real life of the axle.
Keywords: Engineering; Mathematics